The Role of Academic Courses in Media Colleges in Enabling Students to Understand Media Education (An Applied Study on a Sample of Students from the Faculty of Media at the University of the Middle East) - Oreqat, Ahmad; Alrajab, Mahmoud; Badri, Hani (Dirasat: Human and Social Sciences, 2021)
This study aims to identify the role of academic courses in media colleges in enabling students to understand the concept of media education, and the study was based on the concept of media education, and the study used the descriptive approach in the aspect of the survey of the masses of students of the Faculty of Media at the Middle East University, and gathered information through the study tool questionnaire And, the randomly chosen study sample consisted of 105 students, 35% of the college’s total of 307 students, enrolled in the second semester of 2019-2020. The study found that the degree of the role has come average (2.32), and that the skills of knowledge of critical thinking have come high and amounted to (2.63), and the rest of the cognitive skills came with an average degree, and that the differences for students to be able to learn the skills of critical thinking, were in favor of the first academic level And for the benefit of the average is acceptable, and that there are no differences between (gender, educational level, and the GPA) and between students being able to understand media education.